Safety and efficacy of lower-sodium oxybate in adults with idiopathic hypersomnia: a phase 3, placebo-controlled, double-blind, randomised withdrawal study - Dauvilliers, Yves; Arnulf, Isabelle; Foldvary-Schaefer, Nancy; Morse, Anne Marie; Šonka, Karel; Thorpy, Michael J; Mignot, Emmanuel; Chandler, Patricia; Parvataneni, Rupa; Black, Jed; Sterkel, Amanda; Chen, Dan; et al. (The Lancet. Neurology, 2022)
BACKGROUND: Idiopathic hypersomnia is a central hypersomnolence disorder mainly characterised by excessive daytime sleepiness, with prolonged night-time sleep and pronounced sleep inertia. Until August, 2021, no medication had regulatory approval for the treatment of idiopathic hypersomnia. This study aimed to evaluate the safety and efficacy of lower-sodium oxybate in idiopathic hypersomnia. METHODS: This was a phase 3, multicentre (50 specialist sleep centres; six EU countries and the USA), placebo-controlled, double-blind, randomised withdrawal study. Participants (aged 18-75 years) with idiopathic hypersomnia (meeting criteria from the International Classification of Sleep Disorders, 2nd or 3rd editions) began lower-sodium oxybate treatment (oral solution once or twice nightly) in an open-label titration and optimisation period (10-14 weeks), followed by a 2-week, open-label, stable-dose period. After these open-label periods, participants were randomised (1:1) by means of an interactive web recognition system, stratified by participants' baseline medication use, to either placebo or lower-sodium oxybate (individually optimised dose; range 2·5-9·0 g/night) during a 2-week, double-blind, randomised withdrawal period. To maintain masking of treatment assignment, placebo and lower-sodium oxybate oral solutions were matched in volume, appearance, and taste. During the double-blind, randomised withdrawal period, participants and investigators were unaware of treatment assignments. The primary efficacy endpoint was change in Epworth Sleepiness Scale (ESS) score from the end of the stable-dose period to the end of the double-blind, randomised withdrawal period, which was assessed in the modified intention-to-treat population (defined as all participants who were randomly assigned, took at least one dose of study medication during the double blind, randomised withdrawal period, and had at least one set of post-randomisation assessments for the primary or key secondary endpoints). Adverse events were assessed in the safety population (defined as all participants who took at least one dose of study medication). This study is registered at ClinicalTrials.gov, NCT03533114, and at EU Clinical Trials, 2018-001311-79, and is complete. FINDINGS: Between Nov 27, 2018, and March 6, 2020, 154 participants were enrolled and comprised the safety population. ESS scores decreased from a mean of 15·7 (SD 3·8) at baseline to 6·1 (4·0) by the end of the stable-dose period. After the open-label periods, 115 participants were randomly assigned either placebo (n=59) or lower-sodium oxybate (n=56) and comprised the modified intention-to-treat population. During the double-blind, randomised withdrawal period, ESS scores increased (worsened) in participants randomly assigned to placebo but remained stable in those assigned to lower-sodium oxybate (least squares mean difference -6·5; 95% CI -8·0 to -5·0; p<0·0001). Treatment-emergent adverse events included nausea (34 [22%] of 154), headache (27 [18%] of 154), dizziness (19 [12%] of 154), anxiety (17 [11%] 154), and vomiting (17 [11%] 154). No deaths were reported during the study. INTERPRETATION: Lower-sodium oxybate treatment resulted in a clinically meaningful improvement in idiopathic hypersomnia symptoms, with an overall safety profile consistent with that reported for narcolepsy. Lower-sodium oxybate was approved in August, 2021, by the US Food and Drug Administration for the treatment of idiopathic hypersomnia in adults. FUNDING: Jazz Pharmaceuticals.
Keywords: dospělí; Adult; výsledek terapie; mladý dospělý; Adolescent; lidé; dvojitá slepá metoda; Treatment Outcome; Sodium Oxybate; Double-Blind Method; idiopatická hypersomnie; Aged; Young Adult; lidé středního věku; Disorders of Excessive Somnolence; poruchy nadměrné spavosti; senioři; Idiopathic Hypersomnia; oxybát sodný; Middle Aged; mladiství; Humans